2019
DOI: 10.1177/0391398819837696
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative extracorporeal life support on left ventricular assist device outcomes: A comparative study

Abstract: Background: To investigate whether preoperative short-term extracorporeal life support therapy in patients undergoing continuous-flow left ventricular assist device implantation has an impact on the outcome regarding survival and adverse events. Methods: Between January 2011 and May 2018, 100 consecutive patients received HeartMate II, HeartWare, or HeartMate III for end-stage heart failure. Mean age was 64.2 ± 10.3 years. Three patient groups were identified: without preoperative extracorporeal life support (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…A recent report from Germany found that redo sternotomy increased the risk of mortality, blood product transfusion, hepatic and renal dysfunction and ischaemic stroke after VAD implant compared to patients with no previous sternotomy (9). In a separate publication, the same authors found preoperative ECMO to be associated with worse survival, increased right heart failure, respiratory failure and renal failure (10). In our series, five (15%) patients were redo sternotomies, and six (18%) were…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…A recent report from Germany found that redo sternotomy increased the risk of mortality, blood product transfusion, hepatic and renal dysfunction and ischaemic stroke after VAD implant compared to patients with no previous sternotomy (9). In a separate publication, the same authors found preoperative ECMO to be associated with worse survival, increased right heart failure, respiratory failure and renal failure (10). In our series, five (15%) patients were redo sternotomies, and six (18%) were…”
Section: Discussionsupporting
confidence: 45%
“…Those reports excluded patients requiring concomitant procedures, mechanical right sided support, pre VAD mechanical support such as ECMO and redo sternotomies. All of these conditions are well known to increase mortality and morbidity in VAD recipients (9,10). A recent report from Germany found that redo sternotomy increased the risk of mortality, blood product transfusion, hepatic and renal dysfunction and ischaemic stroke after VAD implant compared to patients with no previous sternotomy (9).…”
Section: Discussionmentioning
confidence: 99%
“…Our experience with the ECPELLA concept was previously published from our group. 3 Also, we described different bridging strategies 4 and modern minimally invasive techniques of ECLS implantation 5 in our numerous previously published works.…”
Section: Venoarterial Extracorporeal Life Supportmentioning
confidence: 99%
“…The use of venovenous (VV)‐ECLS for isolated pulmonary support has been gaining ground . ECLS is being increasingly used as a bridge for decision, recovery, durable mechanical circulatory support, or heart/lung transplantation …”
Section: Introductionmentioning
confidence: 99%